A NOVEL METHOD OF MEDICAL CLASSIFICATION USING PARALLELIZATION ALGORITHMS - MOCHURAD, LESIA; ILKIV, ANDRII (Computer systems and information technologies, 2022)
Methods of machine learning in the medical field are the subject of significant ongoing research, which mainly focuses on modeling certain human actions, thought processes or disease recognition. Other applications include biomedical systems, which include genetics and DNA analysis. The purpose of this paper is the implementation of machine learning methods – Random Forest and Decision Tree, further parallelization of these algorithms to achieve greater accuracy of classification and reduce the time of training of these classifiers in the field of medical data processing, determining the presence of human cardiovascular disease. The paper conducts research using machine learning methods for data processing in medicine in order to improve the accuracy and execution time using parallelization algorithms. Classification is an important tool in today's world, where big data is used to make various decisions in government, economics, medicine, and so on. Researchers have access to vast amounts of data, and classification is one of the tools that helps them understand data and find certain patterns in it. The paper used a dataset consisting of records of 70000 patients and containing 12 attributes. Analysis and preliminary data preparation were performed. The Random Forest algorithm is parallelized using the sklearn library functional. The time required to train the model was reduced by 4.4 times when using 8 parallel streams, compared with sequential training. This algorithm is also parallelized based on CUDA. As a result, the time required to train the model was reduced by 83.4 times when using this technology on the GPU. The paper calculates the acceleration and efficiency coefficients, as well as provides a detailed comparison with a sequential algorithm.